Standard essential patents: Who is really holding up (and when)? - Gregor Langus; Vilen Lipatov; Damien Neven (Graduate Institute of International and Development Studies, 2013)
This paper analyzes the effect of injunctions on royalty negotiations for standard essential patents. We develop a model in which courts grant injunctions only when they have sufficient evidence that the prospective licensee is unwilling, in line with the way we understand Courts to operate in Europe. In such a framework the prospective licensee has a powerful strategic tool: the offers that he makes to the patent holder will affect the royalty rate that the Court may adopt as well as the probability of being subject to injunctions (and the liability for litigation costs). We find that despite the availability of injunctions, the holder of a sufficiently weak patent will end up accepting below FRAND rates, in particular when litigation cost are high. We also find that the prospective licensee will sometimes prefer to litigate and the holder of a sufficiently strong patent will always end up in litigation by rejecting offers below FRAND. This arises in particular when the prospective licensee has little to fear from being found unwilling, namely when the trial takes time (so that the threat of injunctions is less powerful),andwhen litigation costs are low. Importantly, we thus find that hold up (royalties above the fair rate) as well as reverse hold up (royalties below the fair rate) may arise in equilibrium.
Keywords: K41; L49; O34; 330; standard essential patent; injunctions; hold up; reverse hold up; Patent; Patentrecht; Rechtsdurchsetzung; Dauer; Lizenz; Europa; USA